Run training vs cross training: Influence of increased training on running economy, foot impact shock, and run performance - Pizza, G. X.; Flynn, M. G.; Starling, R. D.; Brolinson, P. G.; Sigg, J.; Kubitz, E. R.; Davenport, R. L. (International Journal of Sports Medicine, 1995)
After 30 days of normal training, male runners (N = 11) were subjected to 14 days of reduced training (80% of normal). Ss then ran on 10 consecutive days (100% of normal) as well as performing 8 additional morning workouts of the same volume and intensity. The morning sessions were performed on a treadmill or cycle ergometer so that a comparison between specific training and cross-training could be made. Running economy, foot impact shock, and lactate were assessed during a submaximal treadmill run before and after the 10-day period. Following the submaximal assessment, a 5 km time trial on the treadmill was performed. After cross-training VO2max was significantly higher than after specific run-training indicating a detrimental effect. No significant changes occurred in run performance, resting heart rate, or blood pressure. Both training programs had similar effects on other measures: RER, carbohydrate oxidation, and lactate were significantly lower, and foot impact was significantly higher. Implication: Cross-training (cycling) in periods of increased run-training loads was detrimental to running economy and is not a beneficial training alternative.